2010
DOI: 10.1111/j.1574-695x.2010.00700.x
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm-like structures and pathogenicity ofEscherichia hermanniiYS-11, a clinical isolate from a persistent apical periodontitis lesion

Abstract: Escherichia hermannii, formerly classified as enteric group 11 of Escherichia coli, is considered to be nonpathogenic. In this report, we described some of the pathogenic properties of a viscous material-producing E. hermannii strain YS-11, which was clinically isolated from a persistent apical periodontitis lesion. YS-11 possessed cell surface-associated meshwork-like structures that are found in some biofilm-forming bacteria and its viscous materials contained mannose-rich exopolysaccharides. To further exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…If allowed to progress, apical periodontitis can cause the destruction of supporting connective tissues and bones, ultimately resulting in tooth loss. The ability to produce extracellular matrix and to form biofilms is recently considered to be crucial for microorganisms that are present in a root canal to resist the intraroot canal procedures of disinfection, to occupy apical foramina of teeth, and to cause persistent chronic inflammatory lesions [9,[12][13][14]. For future studies to genetically clarify the mechanism of matrix production, we have determined a complete genome sequence of DY-18 with a combined strategy of pyrosequencing and paired-end sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…If allowed to progress, apical periodontitis can cause the destruction of supporting connective tissues and bones, ultimately resulting in tooth loss. The ability to produce extracellular matrix and to form biofilms is recently considered to be crucial for microorganisms that are present in a root canal to resist the intraroot canal procedures of disinfection, to occupy apical foramina of teeth, and to cause persistent chronic inflammatory lesions [9,[12][13][14]. For future studies to genetically clarify the mechanism of matrix production, we have determined a complete genome sequence of DY-18 with a combined strategy of pyrosequencing and paired-end sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…Complementation of this gene to the transposant restored and dramatically augmented the formation of meshwork structures. Our studies using an abscess model in mice indicated that this EPS phenotype might be involved in the pathogenicity of this organism [36]. Likewise, as described above, EPS productivity could be associated with P. intermedia and P. nigrescens pathogenicity [7,8].…”
Section: Discussionmentioning
confidence: 94%
“…[33] reported that Aggregatibacter actinomycetemcomitans has a gene cluster which is homologous to E. coli pgaABCD and encodes the production of poly-ß-1,6-GlcNAc (PGA) [34]. Rothia mucilaginosa DY-18 [35] and Escherichia hermannii YS-11 [36] isolated from persistent apical periodontitis lesions produced EPS and exhibited cell surface meshwork structures. The meshwork structures of E. hermannii YS-11 disappeared when wzt , one of the ABC-transporter genes, was disrupted by transposon random insertion mutagenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The species was felt to be non-pathogenic except in immunocompromised hosts. Yamanaka et al in 2009 demonstrated strains that were able to produce mannose-rich exo-polysaccharides and mesh-like structures, similar to some biofilm forming bacteria, suggesting a mechanism of pathogenicity of E. hermannii that lends itself well to development of CRBSIs [4]. …”
Section: Introductionmentioning
confidence: 99%